Reification as a Recognition Oblivion. Notes for a Review of the Idea of Reification of Axel Honneth (Andamios, Revista de Investigación Social, 2014)
This work aims at analyzing the scopes and limitations of the reformulation which Axel Honneth proposed of the idea of reification during his Tanner lectures in 2005. In order to defend the contributions which a concept of reification as forgetfulness of recognition may embrace, Honneth´s proposal is rebuilt as opposed to the great number of objections it has received. The central argument here is to show that the weaknesses of Honneth´s reification have to do with the weaknesses of his “receptive model” of recognition. As a consequence this work explores the possibility of substituting the Honnethian concept of recognition with an onthological-analytical one to outline then the scope of a reification understood as gradual moments of amnesia.
Keywords: Reification; forgetfulness; recognition; Axel Honneth; amnesia